2015
DOI: 10.1097/cji.0000000000000090
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Programmed Death Ligand 1–derived Peptides Capable of Inducing Cancer-reactive Cytotoxic T Lymphocytes From HLA-A24+ Patients With Renal Cell Carcinoma

Abstract: Molecular therapy targeting tumor angiogenesis has been the standard treatment for metastatic renal cell carcinoma (mRCC). However, despite their significant antitumor effects, most of patients with mRCC have not been cured. Under such circumstances, anticancer immunotherapy has been considered a promising treatment modality for mRCC, and cancer-reactive cytotoxic T lymphocytes (CTLs) are the most powerful effectors among several immune cells. However, anticancer CTLs can be inhibited by several immune inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 26 publications
(101 reference statements)
1
27
0
Order By: Relevance
“…Neutrophils can promote adhesion and tumoral seeding through the secretion of circulating growth factors [17, 18]. Lymphocytes display a significant antitumoral role by inducing cytotoxic cell death and inhibiting tumor cell proliferation and migration, instituting the host's immune response to cancer [1920]. Therefore, inflammation deeply influences cancer microenvironment that supports cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils can promote adhesion and tumoral seeding through the secretion of circulating growth factors [17, 18]. Lymphocytes display a significant antitumoral role by inducing cytotoxic cell death and inhibiting tumor cell proliferation and migration, instituting the host's immune response to cancer [1920]. Therefore, inflammation deeply influences cancer microenvironment that supports cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, PD-L1 molecule which is expressed at high level in various cancer types including RCC was chosen as a target for anticancer immunotherapy. Minami et al identified new HLA-A24+ restricted PD-L1 peptides that could be used for peptide-based anticancer vaccines for metastatic RCC patients (24). One of the limitations to implementing this approach is expression of PD-L1 on non-cancer cells, with the risk that PD-L1-recognizing CTLs could attack normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphocytes represent the cellular basis of cancer immunosurveillance. Compelling evidence indicates that lymphocytes induce cytotoxic cell death and inhibit tumor cell proliferation and migration, thereby dictating the host's immune response to cancer [55]. Decreased lymphocyte counts may lead to downregulation of the immune response against cancer.…”
Section: Discussionmentioning
confidence: 99%